THE ALTERNATIVE STRATEGIES FOR TEACHING READING SKILL FOR EFL STUDENTS - Muhammad Khairi Ikhsan (Fakultas Bahasa dan Seni UNP, 2017)
One thing that can not be denied by the English teachers is teaching English skills. One of the skills that should be taught by the teacher is reading skill. For EFL students, reading is considered as a complicated skill to be comprehended. They tend to have problems to master this skill. There are some common problems made by the EFL students related to reading. For instance, they are difficult to understand the text and find the information from the texts given, and also its hard for them to determine the main ideas of the text. Besides, from the teacher’s perspective, they commonly not applying some appropriate strategies to teach reading. So, reading activities in the classroom sometimes supposed to be boring. Therefore, this paper is aimed at showing some strategies that can be applied by the teachers to make reading activities in the classroom become an interesting one